Latvijas Universitātes tradīcija – svētku dievkalpojumi - Klišāne, Paula (LU Muzejs, 2020)
Latvijas Universitātes Muzeja krājums glabā atmiņas par vienu no tradīcijām Alma Mater – Latvijas Universitātes dibināšanas svētku dievkalpojumu programmas. Kopumā saglabājušās sešas – piecas no starpkaru perioda (1918-1940) un viena no Latvijas Universitātes astoņdesmit gadu jubilejas 1999. gadā. Visi svētbrīži notikuši Doma baznīcā, kas ir arī Latvijas arhibīskapa katedrāle.

The collection of the Museum of the University of Latvia preserves memories of one of the traditions of the Alma Mater - the University of Latvia's founding celebration Church service programms. There are six of them - five from the interwar period (1918-1940) and one from the 80th anniversary of the University of Latvia in 1999. All the services were held in the Cathedral Church, which is also the cathedral of the Archbishop of Latvia.
Keywords: Research Subject Categories::HUMANITIES and RELIGION::Religion/Theology::History of religion; Latvijas Universitāte; Reliģija; Dievkalpojums; Apaļas jubilejas; The University of Latvia; Religion; Church service; Anniversaries